On the biostratigraphic relevance of a new record of a traversodontid cynodont in southern Brazil (Candelária Sequence, Upper Triassic) - Roese-Miron, Lívia; Dotto, Pedro Henrique; Medina, Thais Gotuzzo de Menezes; Da-Rosa, Átila Augusto Stock; Müller, Rodrigo Temp; Kerber, Leonardo (Palaeoworld, 2025)
The Várzea do Agudo is an Upper Triassic site of the Candelária Sequence of Southern Brazil that boasts an extensive fossil record. It is assigned to the Exaeretodon subzone of the Hyperodapedon Assemblage Zone (AZ) (mid-late Carnian) mainly due to the prevalent presence of the traversodontid Exaeretodon riograndensis — up to now the sole traversodontid discovered at the site. In this study, we report the first record of the traversodontid Siriusgnathus niemeyerorum in the Várzea do Agudo site. The new specimen was excavated from the upper layers of the outcrop. Its identification as S. niemeyerorum is substantiated by diagnostic features such as a poorly developed interorbital depression, an inconspicuous suborbital process of the jugal, a not deeply concave base of the lambdoidal crest, the distal accessory labial cusp of the upper postcanines more labially oriented than E. riograndensis, and two upper incisors — so far, a trait autapomorphic to the species among traversodontids. The age of the type locality of S. niemeyerorum has been a subject of debate. Whereas the Siriusgnathus-bearing sites had been associated with younger levels than those of the Hyperodapedon AZ, the absence of index fossils hampered proper biostratigraphic approaches. The finding of a S. niemeyerorum specimen in the same site as E. riograndensis poses a challenging scenario for the biostratigraphy of the fossiliferous outcrops of the municipality of Agudo. It is noteworthy, however, that the new specimen was excavated above the layers yielding E. riograndensis. This raises the question of whether the fossiliferous stratum of the Várzea do Agudo site was deposited in a single event or in a short period, or if it reflects two different time horizons. In the case of the latter, the existence of early Norian sites with distinct faunal composition near the Siriusgnathus-bearing sites could imply the existence of an intermediate fauna between this AZ and the Exaeretodon subzone of the Hyperodapedon AZ, of which S. niemeyerorum would be a constituent. Considering this context, this study discusses the possible biostratigraphic implications of the new record for the biostratigraphy of the sites of the Candelária Sequence.